Annual ADEA Survey of Dental School Seniors: 2015 Graduating Class. Issue 5 (1st May 2016) - Wanchek, Tanya; Cook, Bryan J.; Anderson, Eugene L.; Valachovic, Richard W.
Abstract : This report summarizes and analyzes the results of the American Dental Education Association (ADEA) Survey of Dental School Seniors administered to seniors graduating in 2015. Data were collected from 60 of 61 U.S. dental schools with graduating seniors. The response rate was 83% (4, 827 respondents). Where appropriate, results from prior years are included in this report to allow for comparisons over time. The survey asked students a range of questions concerning their motivations for attending dental school, experience while in dental school, educational debt incurred before and during dental school, and plans following graduation. The results provide insight into the future dental workforce and how well students perceive that schools are meeting their needs. Over the past 15 years, educational debt has nearly tripled at public schools and more than doubled at private schools. However, 12.4% of 2015 seniors reported graduating with no educational debt, an increase from 10.7% in 2014. Nearly half of the 2015 seniors planned to enter private practice dentistry (49.3%), and 34.3% planned to enter graduate school/residence/internship. Although very few seniors planned to teach immediately, the majority planned to teach later in their careers. Over half of American Indian/Alaska Native seniors planned to locate in rural areas or small towns, while over half of Black/African American seniors planned to work in mid‐sized cities or the urban fringe. A majority (53.7%) responded that they would definitely or probably work with underserved populations at some point after graduation. Together these, as well as other results from the survey, provide a window into the dental school experience as perceived by the graduating class of 2015.